β-catenin activity in late hypertrophic chondrocytes locally orchestrates osteoblastogenesis and osteoclastogenesis - Houben, Astrid; Kostanova-Poliakova, Daniela; Weissenboeck, Martina; Graf, Julian; Teufel, Stefan; Mark, Klaus; Hartmann, Christine (Development, 2016)
Trabecular bone formation is the last step in endochondral ossification. This remodeling process of cartilage into bone involves blood vessel invasion and removal of hypertrophic chondrocytes (HTCs) by chondroclasts and osteoclasts. Periosteal- and chondrocyte-derived osteoprogenitors utilize the leftover mineralized HTC matrix as a scaffold for primary spongiosa formation. Here, we show genetically that ?-catenin (encoded by Ctnnb1), a key component of the canonical Wnt pathway, orchestrates this remodeling process at multiple levels. Conditional inactivation or stabilization of ?-catenin in HTCs by a Col10a1-Cre line locally modulated osteoclastogenesis by altering the Rankl:Opg ratio in HTCs. Lack of ?-catenin resulted in a severe decrease of trabecular bone in the embryonic long bones. Gain of ?-catenin activity interfered with removal of late HTCs and bone marrow formation, leading to a continuous mineralized hypertrophic core in the embryo and resulting in an osteopetrotic-like phenotype in adult mice. Furthermore, ?-catenin activity in late HTCs is required for chondrocyte-derived osteoblastogenesis at the chondro-osseous junction. The latter contributes to the severe trabecular bone phenotype in mutants lacking ?-catenin activity in HTCs.
EVALuna2:10223